2017
DOI: 10.1016/j.comppsych.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity, age of onset and suicidality in obsessive–compulsive disorder (OCD): An international collaboration

Abstract: In this large cross-continental study, comorbidity in OCD was common. The high rates of comorbid major depression and anxiety disorders emphasize the need for clinicians to assess and monitor for these disorders. Earlier ages of onset of OCD, specific phobia and social phobia may indicate some relatedness between these disorders, but this requires further study. Although there do not appear to be significant cultural variations in rates or patterns of comorbidity and suicidality, further research using similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
114
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(129 citation statements)
references
References 22 publications
11
114
1
3
Order By: Relevance
“…The observed increase of attempted and completed suicide in prospective studies, especially the one from Fernandez et al 2017, is comparable to the reports from previous crosssectional and retrospective studies: Data from 3711 adult patients with primary OCD that came from several countries indicated that suicidal ideation within the last month was reported by 6.4% (n = 200) of patients with OCD and a lifetime history of suicide attempt was observed in 9.0% (n = 314) (Brakoulias et al 2017). In agreement, patients with a previous suicide attempt had significantly higher rates of comorbid psychiatric disorders (Dell'Osso et al 2017).…”
Section: Outcome Of Literature Searchsupporting
confidence: 82%
See 1 more Smart Citation
“…The observed increase of attempted and completed suicide in prospective studies, especially the one from Fernandez et al 2017, is comparable to the reports from previous crosssectional and retrospective studies: Data from 3711 adult patients with primary OCD that came from several countries indicated that suicidal ideation within the last month was reported by 6.4% (n = 200) of patients with OCD and a lifetime history of suicide attempt was observed in 9.0% (n = 314) (Brakoulias et al 2017). In agreement, patients with a previous suicide attempt had significantly higher rates of comorbid psychiatric disorders (Dell'Osso et al 2017).…”
Section: Outcome Of Literature Searchsupporting
confidence: 82%
“…In a recent large multinational study, suicidal ideation within the last month was reported by 6.4% (n = 200) of patients with OCD, a lifetime history of previous suicide attempts was observed in 9.0% (n = 314) (Brakoulias et al 2017). Crosssectional studies reveal that OCD is not only associated with a high risk of depression but also of recent suicidal behaviour (Chaudhary et al 2016).…”
mentioning
confidence: 99%
“…As such, these dimensions provide a useful framework in which emotion-involvement in OCD symptoms can be studied [39]. Finally, given the overlap at the conceptual, etiological, and phenomenological level between OCD and the anxiety disorders [40,41], studies examining potential emotion-related motivators in individuals with OCD should include anxiety disordered comparison groups to help distinguish between potentially OCD-specific, anxiety-specific, and transdiagnostic emotional processes.…”
Section: Introductionmentioning
confidence: 99%
“…While obsessive-compulsive symptoms lie on a continuum (Abramowitz et al 2014), OCD affects 2-3% of the population (e.g. Ruscio et al 2010) and has a high comorbidity with depression and anxiety disorders (Brakoulias et al 2017;Macy et al 2013;Ruscio et al 2010).…”
mentioning
confidence: 99%